2008
DOI: 10.1182/blood-2008-05-157859
|View full text |Cite
|
Sign up to set email alerts
|

Trisomy 21 enhances human fetal erythro-megakaryocytic development

Abstract: IntroductionTransient myeloproliferative disorder (TMD) occurs in 10% to 20% of newborns with Down syndrome (DS) and usually resolves after birth. However, approximately 30% of TMD patients develop acute megakaryoblastic leukemia (AMKL) within 4 years, suggesting that TMD is a premalignant disorder and that both diseases originate in the fetus. 1-4 DS TMD and AMKL blasts harbor somatic mutations of GATA1, which encodes an essential hematopoietic transcription factor. 5-7 These mutations occur in exon 2 and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
120
1
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 119 publications
(139 citation statements)
references
References 18 publications
17
120
1
1
Order By: Relevance
“…While the current study focuses on the role of GATA1s mutations in erythropoiesis, our findings also provide insights into how these mutations interact with T21. Previous work has shown that T21 augments erythropoiesis in primary fetal cells (61)(62)(63) and iPSCs (18,64). Here, we confirm these findings in T21/WT GATA1 iPSCs and demonstrate that GATA1s overrides the erythropoietic effects of T21 in isogenic double-mutant T21/GATA1s iPSCs derived from 2 different patients with TMD.…”
Section: Discussionsupporting
confidence: 88%
“…While the current study focuses on the role of GATA1s mutations in erythropoiesis, our findings also provide insights into how these mutations interact with T21. Previous work has shown that T21 augments erythropoiesis in primary fetal cells (61)(62)(63) and iPSCs (18,64). Here, we confirm these findings in T21/WT GATA1 iPSCs and demonstrate that GATA1s overrides the erythropoietic effects of T21 in isogenic double-mutant T21/GATA1s iPSCs derived from 2 different patients with TMD.…”
Section: Discussionsupporting
confidence: 88%
“…Particular aneuploidies in conjunction with other specific genomic alterations could also facilitate the development of specific cancers. For example, analyses of individuals with DS demonstrate that trisomy 21 is sufficient to bias differentiation in the human fetal liver, leading to a relative expansion of myeloid cells (Chou et al 2008;TunstallPedoe et al 2008). This bias can progress to a transient myeloproliferative disorder (TMD) (Gamis and Smith 2012) and eventually AML if a cooperating GATA1 mutation is also present (Hitzler 2003;Mundschau et al 2003).…”
Section: H/hmentioning
confidence: 99%
“…However, none of these mouse strains develop TL and AMKL, indicating that additional genetic abnormalities are required to cause leukemia. In humans as well, trisomy 21 itself has been shown to disturb fetal liver, but not bone marrow, hematopoiesis, enhance production of megakaryocyte/erythroid progenitors (MEPs), which may be susceptible to acquisition of other genetic abnormalities, and predispose these cells to DS-related leukemias (Chou et al, 2008;De Vita et al, 2008;Tunstall-Pedoe et al, 2008). These data support the model that the genes on chromosome 21 play essential roles in the development of these disorders and trisomy 21 is the first step of myeloid leukemogenesis in DS.…”
Section: Multistep Model Of Myeloid Leukemogenesis In Children With Dsmentioning
confidence: 63%